Healthcare Professionals' Views on the Management of Medication Complexities in the Elderly With Mental Health Disorders: A Cross-Sectional Study - Aguiar, João Pedro; Gama Marques, João; Leufkens, Hubert G. M.; Alves da Costa, Filipa (Frontiers in Psychiatry, 2022)
Background: Many challenges in elderly pharmacotherapy are identified, including the use of Potentially Inappropriate Medications (PIMs) which may increase the odds of adverse events, especially in elderly patients with mental health disorders (e.g., behavioral, and psychological symptoms of dementia – BPSD, schizophrenia, bipolar disorder). However, information on the knowledge and practice of healthcare professionals (HCPs) about this topic is still scarce. Methods: A cross-sectional study was undertaken from July-October 2019. An online questionnaire was specifically designed and validated for this study. We sought HCPs (physicians, pharmacists, and nurses) worldwide, using (a) social media, via Facebook, Twitter, and LinkedIn; and (b) email contacts of the research team (convenience sample). Either way participants were asked to share on their social media or via e-mail the questionnaires with other HCPs (snowballing sample). The survey accessed two main domains: knowledge and practice. Knowledge was evaluated by self-report (perceived knowledge by a 5-item Likert confidence scale) and using three clinical cases, scored between 0-30 points (each one rated from 0-10 points; real knowledge). Barriers in clinical practice were evaluated using a 5-item Likert scale judging practitioners' opinion. Results: A total of 165 questionnaires were collected. HCPs were mainly female (n=114; 69.1%), with a mean age of 35.3±11.3 years old. Seventy-two percent (n=118) were pharmacists, 21.1% (n=35) were physicians, and 7.3% (n=12) nurses. There was a weak correlation, albeit significant, between perceived and real knowledge (r=0.199; p=0.001). The mean score of the clinical vignettes regarding elderly patients with dementia and bipolar disorder were 4.59±4.08 and 4.86±2.97 points, respectively. Most HCPs were classified as having an intermediate knowledge (n=100; 60.6%) regarding medication complexities in the elderly with mental disorders. Most HCPs agreed that lack of time (81.6%; n=138), lack of education and training on elderly pharmacotherapy (72.2%; n=122), and lack of tools adapted to daily practice (61.8%; n=105) were the main barriers. Conclusions: Most of the HCPs felt confident to manage medication complexities in elder patients with mental disorders, but only a minority obtained a good score in the knowledge assessment test. The main barriers identified included structural barriers (tools unfit for practice) and process barriers (time).